A COMPLEMENTARY APPROACH ON OLFACTORY DYSFUNCTION IN PARKINSONS DISEASE- RETROSPECTIVE OBSERVATIONAL STUDY - Nair Sandeep Damodharan; Vijayagopal Sunil Kumar; Przuntek Horst; Webering Nadine; Hegelmaier Tobias (International Journal of Ayurveda and Pharma Research, 2020)
Olfactory dysfunction is a frequent non-motor symptom of Parkinson’s disease (PD) that involves deficits in odour detection, discrimination, and identification. Hyposmia may be related to neuronal degeneration with deposition of alpha-synuclein in primary olfactory areas as a very early component of the pathology of PD. Olfactory dysfunction also known as Gandhajnana or Gandhanaasha in Ayurveda is a result of improper functioning of different Vatasdue to either degeneration of Dhathus (Tissues) or obstruction in the normal movement of Vata. We analysed the smell test results within the population of Parkinsons patients admitted in Department of Neurology and Complementary medicine in Evangelical Hospital Hattingen from 2012 till 2017. Patients received the prescribed Allopathy and Ayurveda treatment for their ailments along with Ayurveda diet, Ayurveda massage and purification therapies. The primary and the only outcome measure was to assess the results of smelling sensation of the Parkinson’s patients already conducted by a Smell test with Sniffing Sticks supplied by Burghart Messtechnik. A paired t-test was conducted to compare scores obtained in smell test before and after treatment in each group separately. There was a significant difference in the scores of smell test in two groups. Results suggest that patients, treated first with Vasthi and then Ksheerabala oil Nasya showed significant improvement in the scores of smell test (t=-2.509, p= 0.017). The results of patients, treated with only Vasthi also showed significant improvement in the scores of smell test (t=-2.007, p= 0.053).